Gut microbiota composition alteration analysis and functional categorization in children with growth hormone deficiency - Huang, Congfu; Meng, Dongming; Li, Yinhu; Lu, Shiyang; Yang, Wei; Wu, Bin; Chen, Shufen; Yang, Zhenyu; Liu, Haiying (Frontiers in Pediatrics, 2023)
Objective: To study changes in the gut microbiota (GM) composition and functions in children with growth hormone deficiency by high-throughput sequencing. Methods Thirty-three GHD children diagnosed in Longgang District Maternity and Child Health Hospital as the disease group, and 24 healthy children of the same age as the control group. Total DNA was extracted and amplified from stool samples obtained from all subjects. High-throughput sequencing technology was used to analyze GM composition and functions. Results: The GM from the two groups of children showed significant differences in α-diversity (P<0.05). In comparison with the control group, Bacteroidetes was significantly higher (45.96% vs 65.71%) and the Firmicutes count was significantly lower (47.09% vs 25.20%) at the phylum level; at the genus level, the abundance of Prevotella in the disease group was significantly higher (3.16% vs 20.67%) and that of Lachnospiracea incertae sedis, Clostridium XlVa, and Megamonas was lower (6.576% vs 1.75%; 4.51% vs 0.80%; 5.08% vs 2.02%, respectively). GM functions, including Membrane_Transport, Energy_Metabolism, Poorly_Characterized, Metabolism_of_Cofactors_and_Vitamins, Glycan_Biosynthesis_and_Metabolism, Transcription, Folding_Sorting_and_Degradation, significantly changed in the disease group. The abundance of various GM was correlated with endocrine hormones. Conclusion: GM is significantly altered in children with growth hormone deficiency, which may affect the level of energy metabolism and endocrine hormones and consequently lead to growth restriction.